2016
DOI: 10.1016/j.optcom.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Time-delay signatures in multi-transverse mode VCSELs subject to double-cavity polarization-rotated optical feedback

Abstract: Time delay (TD) signatures are studied experimentally in orthogonal polarizations and in individual transverse modes respectively in a VCSEL operating with three transverse modes. Different types of concealment of the TD signatures are observed when the polarization of feedback is rotated through large angles. Effects of feedback strength and external cavity length on the TD signatures are investigated. Weak feedback leads to better concealment of the TD signatures in the dominant polarization. When the roundt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Also, the idea of associating permutations with finite-dimensional partitions of a time series allows the application of this method to time series of arbitrary nature. These remarks agree with the fact that the method of Bandt and Pompe is already widely spread over the scientific community [8,9,10,11,12,13,14,15,16,17].…”
Section: Introductionsupporting
confidence: 85%
“…Also, the idea of associating permutations with finite-dimensional partitions of a time series allows the application of this method to time series of arbitrary nature. These remarks agree with the fact that the method of Bandt and Pompe is already widely spread over the scientific community [8,9,10,11,12,13,14,15,16,17].…”
Section: Introductionsupporting
confidence: 85%
“…Here, in order to quantitatively evaluate the TDS, the ACF and the MI are introduced. The former has been mostly adopted to analyze TDS for its simplicity and fast calculation [8][9][10][11], and the latter, which is based on the probability analysis, is also widely used for TDS identification [12,19]. Figure 4 shows the time series, power spectrum, ACF, and MI for the chaotic output of the FBGF-VCSEL under different feedback strengths of ξ f 0.06 (row 1), 0.22 (row 2) and 0.50 (row 3).…”
Section: Resultsmentioning
confidence: 99%
“…VCSELs subject to suitable optical feedback can generate high Kaplan-Yorke dimension optical chaotic output and then apply to optical-chaos-based communication [1,2,7]. However, the chaotic output from external cavity feedback VCSELs (ECF-VCSELs) usually retains a time-delay signature (TDS) originated from the optical round trip between the VCSEL and the external feedback mirror [8][9][10][11][12][13][14], which may provide some possibilities to reconstruct the system by adopting time-series analysis techniques for delayed systems [15][16][17] and then threaten the system security. As a result, the TDS suppression has been a research hot spot in the field related to chaos generation and applications based on delayed VCSELs in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, Bandt and Pompe [6] have introduced a complexity measure based on the comparison of neighboring values that can be easily applied to any time series. The application of this technique (the permutation entropy) is widely spread over the scientific community [7][8][9][10][11][12][13] mainly because of its simplicity and ability to distinguish among regular, chaotic and random time series. Regarding the particular issue of distinguishing between chaotic and stochastic processes, Rosso et al [14] have shown that the permutation entropy alone is not enough for accomplishing this task.…”
Section: Introductionmentioning
confidence: 99%